Preparation process of anti-corrosion coating matched with outer surface of large oil storage tank
By adopting an anti-corrosion coating system composed of high-solid epoxy zinc-rich primer, high-solid epoxy cloud iron intermediate paint and high-solid polyurethane topcoat, the existing petroleum storage tank's external surface coating is solved, and the coating effect of strong adhesion, good water resistance, good chemical resistance and excellent weather resistance is achieved.
Patent Information
- Application Number
- CN202411949376.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
The external surface coating of existing petroleum storage tanks has problems such as difficult construction, poor rust resistance, weak flexibility and penetration resistance, low adhesion and weather resistance, resulting in the storage tank protection function being prone to failure.
The anticorrosion coating system consisting of high-solid epoxy zinc-rich primer, high-solid epoxy cloud iron intermediate paint and high-solid polyurethane topcoat is adopted. By reasonably selecting resins, curing agents and additives, and strictly dispersing and stirring operations, we ensure good adhesion between each layer and between the coating and the primer, forming a tightly bonded protective whole.
It significantly improves the adhesion, water resistance, chemical resistance and weather resistance of the outer surface coating of the storage tank, extends the service life and protective effect of the coating, and reduces the risk of corrosion caused by the coating shedding.
Smart Images

Figure BDA0005214488530000101 
Figure BDA0005214488530000121 
Figure BDA0005214488530000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of petrochemical coating, and more specifically, particularly relates to a preparation process of a matching anti-corrosion coating on the outer surface of a large petroleum storage tank. Background Art
[0002] As a key storage container for oil products, oil tanks are always under the dual erosion threat of internal and external environmental media during long-term use. Its exterior has long been exposed to erosion from the natural environment, such as oxygen, moisture in the atmosphere, acid rain and other corrosive media. If the anti-corrosion work of the oil tank is not carried out in time, or the anti-corrosion measures adopted are improper, serious leakage accidents may ensue. This will not only hinder the normal use of oil products, but also cause immeasurable pollution to the surrounding environment. In the long run, whether it is the erosion of the external environment or the corrosion of the internal medium, after a long period of continuous "erosion", the equipment will inevitably be damaged, and even eventually scrapped. What's more serious is that in extreme cases, it may also cause major safety accidents. It can be seen that strengthening the anti-corrosion measures of oil tanks is urgent.
[0003] Focusing on the corrosion problem on the outer surface of existing oil storage tanks, there are many obvious defects at the technical level. First, the bottom coating has the dilemma of difficult surface construction and poor anti-rust performance. During the construction process, the bottom coating is difficult to adhere to the surface of the tank evenly and flatly, resulting in weak local protection, and its insufficient anti-rust ability lays hidden dangers for subsequent corrosion. Second, the flexibility and anti-penetration ability of the intermediate coating are poor. When the storage tank faces external stress changes or corrosive media penetration, the intermediate coating cannot effectively adapt and resist, allowing the corrosive media to easily break through the defense line and erode the inner layer. Third, the adhesion, weather resistance and water resistance of the surface coating are all at a low level. This means that when the surface coating faces multiple tests such as harsh weather conditions, long-term rain immersion and oil contact, it is very easy to peel off, age and other problems, thereby losing its effective protection function for the storage tank.
[0004] In a hot and humid environment, the electrochemical corrosion phenomenon on the outside of the storage tank is particularly prominent, and the degree of corrosion is generally severe. In this environment, the ideal anti-corrosion coating should have excellent performance in many aspects and be able to withstand complex working conditions such as climate change, humidity, high temperature, oil corrosion, acid and alkali corrosion, etc. For ground storage tanks in inland areas, since there may be a certain acidity in the atmosphere, its corrosion effect cannot be ignored, so the acid resistance should be considered when selecting the coating. Ground storage tanks in coastal areas face special challenges due to the higher salinity in the atmosphere, and the coating must have excellent resistance to salt spray corrosion. In summary, actively developing a supporting coating system that meets environmental protection standards, has long-term anti-corrosion characteristics and good weather resistance is of extremely critical strategic significance and practical application value for the external anti-corrosion work of large storage tanks. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a preparation process of a matching anti-corrosion coating for the outer surface of a large-scale oil storage tank, so as to solve the problem that the existing outer surface corrosion of oil storage tanks has many obvious defects at the technical level, such as the difficulty in construction of the base coating and poor rust prevention, the weak flexibility and anti-penetration ability of the intermediate coating, the low adhesion, weather resistance and water resistance of the surface coating, which makes the protection function of the tank easily fail.
[0006] The purpose and efficacy of the preparation process of a large-scale petroleum storage tank outer surface supporting anti-corrosion coating of the present invention are achieved by the following specific technical means:
[0007] A preparation process of a large-scale oil storage tank outer surface supporting anti-corrosion coating, the outer surface supporting anti-corrosion coating is composed of high-solid epoxy zinc-rich primer, high-solid epoxy micaceous iron intermediate paint, and high-solid polyurethane topcoat, comprising the following steps:
[0008] The following steps are involved:
[0009] Step 1. The primer is a high-solid epoxy zinc-rich primer, and its raw materials are divided into component A and component B. The specific composition is as follows:
[0010] The composition of component A by mass is as follows:
[0011] 8-15 parts of epoxy resin;
[0012] The epoxy resin is liquid epoxy resin DER 331;
[0013] 3-5 parts of environmentally friendly solvent;
[0014] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0015] 1-2 parts of thixotropic agent;
[0016] The thixotropic agent is one or a mixture of two or more of organic bentonite 140, bentonite 979, and polyamide wax powder HX-9110; 80 to 82 parts of 1250 mesh filler;
[0017] The filler is zinc powder processed by dry and high-energy ball milling technology and with multi-layer coating;
[0018] 0.01-0.2 parts of single-arm carbon nanotubes;
[0019] Adhesion promoter 0.5-1.5 parts;
[0020] The adhesion promoter is A-187;
[0021] The composition of component B by mass is as follows:
[0022] 40-60 parts of modified phenolic amine curing agent;
[0023] Special amine curing agent 10-30;
[0024] The special amine curing agent is one or more of MD650, MD531E of Meidong, and NX-5454 curing agent of Cardolite;
[0025] 5-15 parts of environmentally friendly solvent;
[0026] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0027] Step 2. The preparation method of high solid epoxy zinc-rich primer is as follows:
[0028] (1) Preparation of component A:
[0029] ①Mix the epoxy resin and environmentally friendly solvent evenly and stir at low speed for 10 to 15 minutes;
[0030] Low speed is 400~600r / min;
[0031] ② Add thixotropic agent and single-arm carbon nanotubes and disperse at medium speed for 10 to 15 minutes;
[0032] Medium speed is 600-800r / min;
[0033] ③ Add filler, disperse at medium speed for 25-40 minutes after adding, and control the temperature at 40-55℃;
[0034] Medium speed is 600-800r / min;
[0035] ④ After the paint cools to room temperature, add adhesion promoter and stir evenly. The fineness requirement is: ≤60μm.
[0036] (2) Preparation of component B:
[0037] ① Add modified phenolic amine curing agent, special amine curing agent and environmentally friendly solvent according to the formula, and stir thoroughly for 15 to 30 minutes at a medium speed of 600 to 800 r / min;
[0038] (3) When using, component A and component B are fully mixed in proportion to obtain a high-solid epoxy zinc-rich primer, and the mass ratio of component A to component B is 12:1 to 26:1;
[0039] Step 3. The middle coating is a high-solid epoxy micaceous iron intermediate paint, and its raw materials are divided into component A and component B. The specific composition is as follows:
[0040] The composition of component A by mass is as follows:
[0041] Epoxy resin 25-35 parts;
[0042] The epoxy resin is liquid epoxy resin E51;
[0043] 2 to 5 parts of active diluent;
[0044] The active diluent is cardanol glycidyl ether;
[0045] 3-8 parts of environmentally friendly solvent;
[0046] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0047] 1-2 parts of thixotropic agent;
[0048] The thixotropic agent is one or a mixture of two or more of organic bentonite 140, bentonite 979, and polyamide wax powder HX-9110;
[0049] 1 to 3 parts of film-forming aid;
[0050] The film-forming aid is hydroxyethyl cellulose;
[0051] 10-20 parts of filler;
[0052] The filler is 800 mesh flake mica iron oxide;
[0053] 15-25 parts of 1250 mesh ultrafine modified barium sulfate;
[0054] 3-6 parts of pigment powder;
[0055] The pigment powder is rutile titanium dioxide;
[0056] The composition of component B by mass is as follows:
[0057] 40-60 parts of polyamide curing agent;
[0058] The polyamide curing agent is one or more of Sanmu's 650, Junjiang's D8115, and Guodu's KH-500 curing agent;
[0059] 10-20 parts of fatty amine curing agent;
[0060] 10-20 parts of environmentally friendly solvent;
[0061] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0062] Step 4. The preparation method of high solid epoxy micaceous iron intermediate paint is as follows:
[0063] (1) Preparation of component A:
[0064] ①Mix epoxy resin, active diluent and environmentally friendly solvent evenly and stir at low speed for 10 to 15 minutes;
[0065] Low speed is 400~600r / min;
[0066] ② Add thixotropic agent and film-forming agent and disperse at high speed for 15 to 25 minutes;
[0067] High speed is 1000~1100r / min;
[0068] ③ Add filler, 1250 mesh ultrafine modified barium sulfate and pigment powder, disperse at high speed for 25-40 minutes after adding, and control the temperature at 40-55℃;
[0069] High speed is 1000~1100r / min;
[0070] (2) Preparation of component B:
[0071] ① Add polyamide curing agent, fatty amine curing agent and environmentally friendly solvent according to the formula, and stir thoroughly at medium speed for 15 to 30 minutes;
[0072] Medium speed is 600-800r / min;
[0073] (3) When using, component A and component B are fully mixed in proportion to obtain a high-solid epoxy micaceous iron intermediate paint, and the mass ratio of component A to component B is 8:1 to 12:1;
[0074] Step 5. The topcoat is a high-solid polyurethane topcoat, and its raw materials are divided into component A and component B. The specific composition is as follows:
[0075] The composition of component A by mass is as follows:
[0076] 40-60 parts of high solid and low viscosity modified hydroxypropylene resin;
[0077] The high-solid, low-viscosity modified hydroxypropylene resin is Diana LR-7765;
[0078] 3-8 parts of environmentally friendly solvent;
[0079] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0080] Thixotropic agent 0.5-2 parts;
[0081] The thixotropic agent is one or a mixture of two or more of fumed silica A200, polyethylene wax slurry 202P, and organosilicon bentonite 979;
[0082] 2 to 6 portions of functional powder;
[0083] The functional powder is 1250 mesh ultrafine polytetrafluoroethylene powder;
[0084] 3 to 8 parts of filler;
[0085] The filler is 1250 mesh ultrafine modified barium sulfate;
[0086] 15-30 parts of pigment powder;
[0087] The pigment is rutile titanium dioxide;
[0088] 0.5-1.5 parts of ultraviolet light absorber;
[0089] The ultraviolet light absorber is 2-(2H-benzotriazole-2-yl)-4,6-di-tert-amylphenol;
[0090] Light stabilizer 0.5-2 parts;
[0091] The light stabilizer is mono(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate;
[0092] The composition of component B by mass is as follows:
[0093] 70-80 parts of HDI trimer curing agent; HDI trimer curing agent is aliphatic polyisocyanate from Bayer;
[0094] 20-30 parts of environmentally friendly solvent;
[0095] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0096] Step 6. The preparation method of high solid polyurethane topcoat is as follows:
[0097] (1) Preparation of component A:
[0098] ①Mix high-solid low-viscosity modified hydroxypropylene resin and environmentally friendly solvent evenly, and stir at low speed for 10 to 15 minutes;
[0099] Low speed is 400~600r / min;
[0100] ② Add thixotropic agent and additives and disperse at medium speed for 10 to 15 minutes;
[0101] Medium speed is 600-800r / min;
[0102] ③ Add fillers, pigment powders and functional powders, disperse at high speed for 25-40 minutes after adding, and control the temperature at 40-55℃;
[0103] High speed is 1000~1100r / min;
[0104] ④ Grind the above slurry into a sand mill until the fineness is ≤25μm;
[0105] ⑤Finally, add the UV absorber and light stabilizer and disperse at medium speed for 10 to 15 minutes;
[0106] Medium speed is 600-800r / min;
[0107] (2) Preparation of component B:
[0108] ① Add HDI trimer curing agent and environmentally friendly solvent according to the formula, and stir thoroughly at medium speed for 15 to 30 minutes;
[0109] Medium speed is 600-800r / min;
[0110] (3) When in use, component A and component B are fully mixed in proportion to obtain a high-solid polyurethane topcoat, and the mass ratio of component A to component B is 6:1 to 10:1.
[0111] Compared with the prior art, the present invention has the following beneficial effects:
[0112] The large-scale oil storage tank outer surface anti-corrosion coating developed by the present invention effectively solves the problems existing in the existing oil storage tank outer surface coating, has many advantages such as strong adhesion, good water resistance, good chemical resistance and excellent weather resistance, and has significant economic and social benefits, and has broad application prospects in the field of oil storage tank protection.
[0113] The primer of the present invention adopts high-solid epoxy zinc-rich primer, and an adhesion promoter A-187 is added to the A component of the primer. At the same time, the filler is treated by dry method and high-energy ball milling technology, and zinc powder with multi-layer coating treatment and single-arm carbon nanotubes are added. These measures effectively improve the adhesion between the primer and the outer surface of the storage tank, so that the entire coating system can be firmly attached to the surface of the storage tank and is not easy to fall off, providing a solid foundation for subsequent coatings and greatly reducing the corrosion risk caused by coating shedding. In addition, in the respective raw material formulas and preparation processes of the middle coating and the top coating, by reasonably selecting components such as resin, curing agent and auxiliary agent, and performing strict dispersion and stirring operations, it is ensured that the coatings and between the coating and the primer have good adhesion, forming a tightly combined protective whole, and effectively resisting the influence of external factors on the adhesion of the coating.
[0114] In the entire anti-corrosion coating system of the present invention, environmentally friendly solvents, such as propylene glycol methyl ether acetate, are selected as the raw materials of each coating. These solvents have low water absorption, which reduces the problem of coating performance degradation caused by solvent water absorption in a humid environment. In addition, the high-solid polyurethane topcoat in the topcoat improves the weather resistance of the coating by adding ultraviolet light absorbers and light stabilizers, such as 2-(2H-benzotriazole-2-yl)-4,6-di-tert-amylphenol and mono(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, so that it can effectively prevent moisture from penetrating into the coating when it is exposed to harsh environments such as rain for a long time, thereby protecting the storage tank from water erosion, and significantly extending the service life and protective effect of the coating.
[0115] The high-solid epoxy zinc-rich primer in the primer of the present invention contains a large amount of specially treated zinc powder, which plays the role of a sacrificial anode in the coating. When the coating is corroded by chemicals, the zinc powder is corroded first, thereby protecting the metal surface of the storage tank from being directly corroded by the chemicals. At the same time, the epoxy resin and curing agent system in the primer also have certain chemical resistance and can effectively resist the corrosion of various chemical substances that may exist around the storage tank. The high-solid epoxy micaceous iron intermediate paint in the middle coating, the flaky mica iron oxide filler and the 1250 mesh ultrafine modified barium sulfate filler and the pigment powder and other ingredients in the A component form a dense protective layer, which can block the penetration of chemicals into the surface of the storage tank, enhance the chemical resistance of the coating system, and ensure that the storage tank maintains a good protective state in a complex chemical environment.
[0116] The ultraviolet light absorber and light stabilizer added to the high-solid polyurethane topcoat of the present invention can effectively absorb and shield ultraviolet rays, prevent ultraviolet rays from damaging the coating, reduce problems such as aging, fading and powdering of the coating, and enable it to maintain good appearance and protective performance during long-term outdoor use. The entire coating system of the present invention can adapt to various severe climatic conditions such as high temperature, low temperature, wind and sand, rain and snow, etc. through the synergistic effect between the layers and the optimized formula and preparation process of each layer itself, and can protect the outer surface of large oil storage tanks in a long-term and stable manner, greatly reducing the possibility of coating failure and tank corrosion caused by climatic factors, and providing reliable protection for the safe operation of oil storage tanks. DETAILED DESCRIPTION
[0117] The following examples are used to further describe the embodiments of the present invention. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0118] Embodiment 1:
[0119] The present invention provides a preparation process of a matching anti-corrosion coating on the outer surface of a large petroleum storage tank, wherein the matching anti-corrosion coating on the outer surface is composed of a high-solid epoxy zinc-rich primer, a high-solid epoxy micaceous iron intermediate paint, and a high-solid polyurethane topcoat, and comprises the following steps:
[0120] The following steps are involved:
[0121] Step 1. The primer is a high-solid epoxy zinc-rich primer, and its raw materials are divided into component A and component B. The specific composition is as follows: Component A consists of the following by mass:
[0122] 8-15 parts of epoxy resin;
[0123] The epoxy resin is liquid epoxy resin DER 331;
[0124] 3-5 parts of environmentally friendly solvent;
[0125] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0126] 1-2 parts of thixotropic agent;
[0127] The thixotropic agent is one or a mixture of two or more of organic bentonite 140, bentonite 979, and polyamide wax powder HX-9110; 80 to 82 parts of 1250 mesh filler;
[0128] The filler is zinc powder processed by dry and high-energy ball milling technology and with multi-layer coating;
[0129] 0.01-0.2 parts of single-arm carbon nanotubes;
[0130] Adhesion promoter 0.5-1.5 parts;
[0131] The adhesion promoter is A-187;
[0132] The composition of component B by mass is as follows:
[0133] 40-60 parts of modified phenolic amine curing agent;
[0134] Special amine curing agent 10-30;
[0135] The special amine curing agent is one or more of MD650, MD531E of Meidong, and NX-5454 curing agent of Cardolite;
[0136] 5-15 parts of environmentally friendly solvent;
[0137] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0138] Step 2. The preparation method of high solid epoxy zinc-rich primer is as follows:
[0139] (1) Preparation of component A:
[0140] ①Mix the epoxy resin and environmentally friendly solvent evenly and stir at low speed for 10 to 15 minutes;
[0141] Low speed is 400~600r / min;
[0142] ② Add thixotropic agent and single-arm carbon nanotubes and disperse at medium speed for 10 to 15 minutes;
[0143] Medium speed is 600-800r / min;
[0144] ③ Add filler, disperse at medium speed for 25-40 minutes after adding, and control the temperature at 40-55℃;
[0145] Medium speed is 600-800r / min;
[0146] ④ After the paint cools to room temperature, add adhesion promoter and stir evenly. The fineness requirement is: ≤60μm.
[0147] (2) Preparation of component B:
[0148] ① Add modified phenolic amine curing agent, special amine curing agent and environmentally friendly solvent according to the formula, and stir thoroughly at medium speed for 15 to 30 minutes;
[0149] Medium speed is 600-800r / min;
[0150] (3) When using, component A and component B are fully mixed in proportion to obtain a high-solid epoxy zinc-rich primer, and the mass ratio of component A to component B is 12:1 to 26:1;
[0151] The properties of the high solid epoxy zinc-rich primer coating prepared in the embodiment of the present invention are shown in Table 1:
[0152] Table 1
[0153]
[0154] Step 3. The middle coating is a high-solid epoxy micaceous iron intermediate paint, and its raw materials are divided into component A and component B. The specific composition is as follows: Component A consists of the following by mass:
[0155] Epoxy resin 25-35 parts;
[0156] The epoxy resin is liquid epoxy resin E51;
[0157] 2 to 5 parts of active diluent;
[0158] The active diluent is cardanol glycidyl ether;
[0159] 3-8 parts of environmentally friendly solvent;
[0160] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0161] 1-2 parts of thixotropic agent;
[0162] The thixotropic agent is one or a mixture of two or more of organic bentonite 140, bentonite 979, and polyamide wax powder HX-9110; 1 to 3 parts of film-forming aid;
[0163] The film-forming aid is hydroxyethyl cellulose;
[0164] 10-20 parts of filler;
[0165] The filler is 800 mesh flake mica iron oxide;
[0166] 15-25 parts of 1250 mesh ultrafine modified barium sulfate;
[0167] 3-6 parts of pigment powder;
[0168] The pigment powder is rutile titanium dioxide;
[0169] The composition of component B by mass is as follows:
[0170] 40-60 parts of polyamide curing agent;
[0171] The polyamide curing agent is one or more of Sanmu's 650, Junjiang's D8115, and Guodu's KH-500 curing agent;
[0172] 10-20 parts of fatty amine curing agent;
[0173] 10-20 parts of environmentally friendly solvent;
[0174] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0175] Step 4. The preparation method of high solid epoxy micaceous iron intermediate paint is as follows:
[0176] (1) Preparation of component A:
[0177] ①Mix epoxy resin, active diluent and environmentally friendly solvent evenly and stir at low speed for 10 to 15 minutes;
[0178] Low speed is 400~600r / min;
[0179] ② Add thixotropic agent and film-forming agent and disperse at high speed for 15 to 25 minutes;
[0180] High speed is 1000~1100r / min;
[0181] ③ Add filler, 1250 mesh ultrafine modified barium sulfate and pigment powder, disperse at high speed for 25-40 minutes after adding, and control the temperature at 40-55℃;
[0182] High speed is 1000~1100r / min;
[0183] (2) Preparation of component B:
[0184] ① Add polyamide curing agent, fatty amine curing agent and environmentally friendly solvent according to the formula, and stir thoroughly at medium speed for 15 to 30 minutes;
[0185] Medium speed is 600-800r / min;
[0186] (3) When using, component A and component B are fully mixed in proportion to obtain a high-solid epoxy micaceous iron intermediate paint, and the mass ratio of component A to component B is 8:1 to 12:1;
[0187] The properties of the high solid epoxy micaceous iron intermediate paint prepared in the embodiment of the present invention are shown in Table 2:
[0188] Table 2
[0189]
[0190]
[0191] Note: The coating thickness for hot water resistance, gasoline resistance, salt spray resistance and chemical medium resistance tests should be 120μm to 160μm
[0192] Step 5. The topcoat is a high-solid polyurethane topcoat, and its raw materials are divided into component A and component B. The specific composition is as follows:
[0193] The composition of component A by mass is as follows:
[0194] 40-60 parts of high solid and low viscosity modified hydroxypropylene resin;
[0195] The high-solid, low-viscosity modified hydroxypropylene resin is Diana LR-7765;
[0196] 3-8 parts of environmentally friendly solvent;
[0197] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0198] Thixotropic agent 0.5-2 parts;
[0199] The thixotropic agent is one or a mixture of two or more of fumed silica A200, polyethylene wax slurry 202P, and organosilicon bentonite 979;
[0200] 2 to 6 portions of functional powder;
[0201] The functional powder is 1250 mesh ultrafine polytetrafluoroethylene powder;
[0202] 3 to 8 parts of filler;
[0203] The filler is 1250 mesh ultrafine modified barium sulfate;
[0204] 15-30 parts of pigment powder;
[0205] The pigment is rutile titanium dioxide;
[0206] 0.5-1.5 parts of ultraviolet light absorber;
[0207] The ultraviolet light absorber is 2-(2H-benzotriazole-2-yl)-4,6-di-tert-amylphenol;
[0208] Light stabilizer 0.5-2 parts;
[0209] The light stabilizer is mono(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate;
[0210] The composition of component B by mass is as follows:
[0211] 70-80 parts of HDI trimer curing agent; HDI trimer curing agent is aliphatic polyisocyanate from Bayer;
[0212] 20-30 parts of environmentally friendly solvent;
[0213] The environmentally friendly solvent is propylene glycol methyl ether acetate;
[0214] Step 6. The preparation method of high solid polyurethane topcoat is as follows:
[0215] (1) Preparation of component A:
[0216] ①Mix high-solid low-viscosity modified hydroxypropylene resin and environmentally friendly solvent evenly, and stir at low speed for 10 to 15 minutes;
[0217] Low speed is 400~600r / min;
[0218] ② Add thixotropic agent and additives and disperse at medium speed for 10 to 15 minutes;
[0219] Medium speed is 600-800r / min;
[0220] ③ Add fillers, pigment powders and functional powders, disperse at high speed for 25-40 minutes after adding, and control the temperature at 40-55℃;
[0221] High speed is 1000~1100r / min;
[0222] ④ Grind the above slurry into a sand mill until the fineness is ≤25μm;
[0223] ⑤Finally, add the UV absorber and light stabilizer and disperse at medium speed for 10 to 15 minutes;
[0224] Medium speed is 600-800r / min;
[0225] (2) Preparation of component B:
[0226] ① Add HDI trimer curing agent and environmentally friendly solvent according to the formula, and stir thoroughly at medium speed for 15 to 30 minutes;
[0227] Medium speed is 600-800r / min;
[0228] (3) When using, component A and component B are fully mixed in proportion to obtain a high-solid polyurethane topcoat, and the mass ratio of component A to component B is 6:1 to 10:1;
[0229] The properties of the high solid polyurethane topcoat coating prepared in the embodiment of the present invention are shown in Table 3:
[0230] Note: The coating system and thickness for testing adhesion, gasoline resistance, salt spray resistance, chemical medium resistance, artificial accelerated aging and freeze-thaw cycles should be determined according to the technical documents or design documents provided by the coating supplier. High-solid epoxy zinc-rich primer 80μm~100μm, high-solid epoxy micaceous iron intermediate paint 120μm~160μm, high-solid polyurethane topcoat 80μm~100μm. Total film thickness 280μm~340μm. Example 2: (a) The preparation method of high-solid epoxy zinc-rich primer is as follows: Preparation of component A: ① Stir 11 parts of liquid epoxy resin DER 331 and 4.9 parts of propylene glycol methyl ether acetate solvent at 400-600r / min for 12min; ② Add 1 part of HX-9110 thixotropic agent and 0.1 part of single-arm carbon nanotubes, and disperse at 600-800r / min for 12min; ③ Add 82 parts of 1200 mesh zinc powder, and disperse at 600-800r / min for 30min, and control the temperature at 40-45℃; ④ Cool to 25-30℃, add 1 part of A-187, stir evenly, and control the fineness to ≤60μm to obtain component A. Preparation of component B: 65 parts of NX-5454 phenolic amine curing agent, 22 parts of 6280 alicyclic amine curing agent and 13 parts of propylene glycol methyl ether acetate solvent were dispersed at a speed of 600-800 r / min for 20 minutes to obtain component B.
[0231] Component A and component B were mixed at a mass ratio of 12:1 to obtain a high-solid epoxy zinc-rich primer, the performance test of which is shown in Table 1:
[0232] Table 1
[0233]
[0234] (II) The preparation method of high solid epoxy micaceous iron intermediate paint is as follows:
[0235] Preparation of component C:
[0236] ① Mix 21 parts of liquid epoxy resin E51, 1 part of cardanol glycidyl ether and 8.5 parts of propylene glycol methyl ether acetate, and stir at 400-600r / min for 20min;
[0237] ② Add 1.5 parts of HX-9110 thixotropic agent and 5 parts of hydroxyethyl cellulose, and disperse at a speed of 1000-1100 r / min for 20 minutes;
[0238] ③ Add 15 parts of 800 mesh flaky mica iron oxide, 18 parts of rutile titanium dioxide and 30 parts of 1250 mesh ultrafine modified barium sulfate, disperse at a speed of 1000-1100 r / min for 30 minutes, and control the temperature at 40-45°C;
[0239] ④ Cool down to 25-30℃, control the slurry fineness ≤60μm, and obtain component C;
[0240] Preparation of component D: 63 parts of D8115 polyamide curing agent, 17 parts of 2636 fatty amine curing agent, 15 parts of propylene glycol methyl ether acetate and 25 parts of DBE solvent were dispersed at a speed of 600-800 r / min for 20 minutes to obtain component D.
[0241] Component C and component D were mixed at a mass ratio of 10:1 to obtain a high-solid epoxy micaceous iron intermediate paint, the performance test of which is shown in Table 2:
[0242] Table 2
[0243]
[0244]
[0245] Note: The coating thickness for hot water resistance, gasoline resistance, salt spray resistance and chemical medium resistance tests is 120μm~
[0246] 160μm.
[0247] (III) The preparation method of high solid polyurethane topcoat is as follows:
[0248] Preparation of component E:
[0249] ① Mix 55 parts of LR-7765, 2 parts of propylene glycol methyl ether acetate and 1 part of DBE solvent evenly, and stir at a speed of 400-600r / min for 12min;
[0250] ② Add 1 part of 140 bentonite and 0.5 parts of A200 fumed silica thixotropic agent, and disperse at a speed of 1000-1100 r / min for 12 minutes;
[0251] ③ Add 5.5 parts of 1250 mesh ultrafine polytetrafluoroethylene powder, 13 parts of 1250 mesh ultrafine modified barium sulfate and 20 parts of rutile titanium dioxide, disperse at a speed of 1000-1100 r / min for 30 minutes, and control the temperature at 40-45°C;
[0252] ④ Send the slurry into the sand mill and grind it to a fineness of ≤25μm;
[0253] ⑤ Cool down to 25-30°C, add 2 parts of 2-(2H-benzotriazole-2-yl)-4,6-di-tert-amylphenol and 1 part of mono(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, and disperse at a speed of 600-800 r / min for 12 minutes to obtain component E.
[0254] Preparation of component F: 82 parts of aliphatic polyisocyanate N3390 and 18 parts of propylene glycol methyl ether acetate are dispersed at a speed of 600-800 r / min for 20 minutes to obtain component F.
[0255] The E component and the F component were mixed at a mass ratio of 6:1 to obtain a high-solid polyurethane topcoat, the performance test of which is shown in Table 3:
[0256] Table 3
[0257]
[0258]
[0259] Note: The coating system and thickness for testing adhesion, gasoline resistance, salt spray resistance, chemical medium resistance, artificial accelerated aging and freeze-thaw cycles should be determined according to the technical documents or design documents provided by the coating supplier. High-solid epoxy zinc-rich primer is 80μm~100μm, high-solid epoxy micaceous iron intermediate paint is 120μm~160μm, and high-solid polyurethane topcoat is 80μm~100μm. The total film thickness is 280μm~360μm.
[0260] Embodiment 3:
[0261] In this embodiment, the difference between component A and embodiment 2 is that the single-arm carbon nanotube is 0.2 parts, and a high-solid epoxy zinc-rich primer is obtained, and its performance test is shown in Table 4:
[0262] Table 4
[0263]
[0264] In this embodiment, the difference between component C and embodiment 2 is that the hydroxyethyl cellulose is 8 parts. A high-solid epoxy micaceous iron intermediate paint is obtained, and its performance test is shown in Table 5:
[0265] Table 5
[0266]
[0267]
[0268] Note: The coating thickness for hot water resistance, gasoline resistance, salt spray resistance and chemical medium resistance tests is 120μm~
[0269] 160μm.
[0270] In this embodiment, the difference between component E and embodiment 2 is that the 1250 mesh ultrafine polytetrafluoroethylene powder is 7 parts. A high solid polyurethane topcoat is obtained, and its performance test is shown in Table 6:
[0271] Table 6
[0272]
[0273]
[0274] Embodiment 4:
[0275] The only difference between this embodiment and embodiment 2 is that the single-arm carbon nanotubes in the high-solid epoxy zinc-rich primer are replaced with graphene.
[0276] The high solid epoxy zinc-rich primer was obtained, and its performance test is shown in Table 7:
[0277] Table 7
[0278]
[0279]
[0280] Embodiment 5:
[0281] The difference between this embodiment and embodiment 2 is that the epoxy resin in the high-solid epoxy micaceous iron intermediate paint is replaced with E20. The high-solid epoxy micaceous iron intermediate paint is obtained, and its performance test is shown in Table 8:
[0282] Table 8
[0283]
[0284]
[0285] Note: The coating thickness for hot water resistance, gasoline resistance, salt spray resistance and chemical medium resistance tests is 120μm~
[0286] 160μm.
[0287] Embodiment 6:
[0288] The only difference between this embodiment and embodiment 2 is that the resin LR7765 in the high-solid polyurethane topcoat is replaced by Fangxin FX-9070.
[0289] The high solid polyurethane topcoat was obtained, and its performance test is shown in Table 9:
[0290] Table 9
[0291]
[0292]
[0293] Note: The coating system and thickness for testing adhesion, gasoline resistance, salt spray resistance, chemical medium resistance, artificial accelerated aging and freeze-thaw cycles should be determined according to the technical documents or design documents provided by the coating supplier. High-solid epoxy zinc-rich primer is 80μm~100μm, high-solid epoxy micaceous iron intermediate paint is 120μm~160μm, and high-solid polyurethane topcoat is 80μm~100μm. The total film thickness is 280μm~360μm.
[0294] Embodiment 7:
[0295] The only difference from Example 2 is that the curing agent NX-5454 in the high-solid epoxy zinc-rich primer is replaced by MD531E.
[0296] The high solid epoxy zinc-rich primer was obtained, and its performance test is shown in Table 10:
[0297] Table 10
[0298]
[0299]
[0300] Embodiment 8:
[0301] The only difference from Example 2 is that the curing agent 2778 in the high-solid epoxy micaceous iron intermediate paint is replaced with Sanmu 650. A high-solid epoxy micaceous iron intermediate paint is obtained, and its performance test is shown in Table 11:
[0302] Table 11
[0303]
[0304]
[0305] Note: The coating thickness for hot water resistance, gasoline resistance, salt spray resistance and chemical medium resistance tests is 120μm~
[0306] 160μm.
[0307] Embodiment 9:
[0308] The only difference from Example 2 is that the isocyanate curing agent in the high-solid polyurethane topcoat is replaced with HT100. A high-solid polyurethane topcoat is obtained, and its performance test is shown in Table 12:
[0309] Table 12
[0310]
[0311]
[0312] Note: The coating system and thickness for testing adhesion, gasoline resistance, salt spray resistance, chemical medium resistance, artificial accelerated aging and freeze-thaw cycles should be determined according to the technical documents or design documents provided by the coating supplier. High-solid epoxy zinc-rich primer is 80μm~100μm, high-solid epoxy micaceous iron intermediate paint is 120μm~160μm, and high-solid polyurethane topcoat is 80μm~100μm. The total film thickness is 280μm~360μm.
[0313] Comparative Example 1
[0314] The difference between this comparative example and Example 2 is that no single-arm carbon nanotubes are added to component A, no hydroxyethyl cellulose is added to component C, and no 1250 mesh ultrafine polytetrafluoroethylene powder is added to component E. The performance tests of the primer, intermediate paint and topcoat obtained are shown in Tables 13, 14 and 15 respectively:
[0315] Table 13
[0316]
[0317]
[0318] Table 14
[0319]
[0320]
[0321] Note: The coating thickness for hot water resistance, gasoline resistance, salt spray resistance and chemical medium resistance tests is 120μm~
[0322] 160μm.
[0323] Table 15
[0324]
[0325] Note: The coating system and thickness for testing adhesion, gasoline resistance, salt spray resistance, chemical medium resistance, artificial accelerated aging and freeze-thaw cycles should be determined according to the technical documents or design documents provided by the coating supplier. High-solid epoxy zinc-rich primer 80μm~100μm, high-solid epoxy micaceous iron intermediate paint 120μm~160μm, high-solid polyurethane topcoat 80μm~100μm. Total film thickness 280μm~360μm.
[0326] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.
Claims
1. A preparation process for a matching anti-corrosion coating on the outer surface of a large petroleum storage tank, characterized in that: The outer surface anti-corrosion coating consists of high-solid epoxy zinc-rich primer, high-solid epoxy micaceous iron intermediate paint, and high-solid polyurethane topcoat, including the following steps: Step 1. The primer is a high-solid epoxy zinc-rich primer, and its raw materials are divided into component A and component B. The specific composition is as follows: The composition of component A by mass is as follows: 8-15 parts of epoxy resin, 3-5 parts of environmentally friendly solvent, 1-2 parts of thixotropic agent, 80-82 parts of 1250 mesh filler, 0.01-0.2 parts of single-arm carbon nanotubes, and 0.5-1.5 parts of adhesion promoter; The composition of component B by mass is as follows: 40-60 parts of modified phenolic amine curing agent, 10-30 parts of special amine curing agent, 5-15 parts of environmentally friendly solvent; Step 2. The preparation method of high solid epoxy zinc-rich primer is as follows: (1) Preparation of component A: ①Mix the epoxy resin and environmentally friendly solvent evenly and stir at low speed for 10 to 15 minutes; ② Add thixotropic agent and single-arm carbon nanotubes and disperse at medium speed for 10 to 15 minutes; ③ Add filler, disperse at medium speed for 25-40 minutes after adding, and control the temperature at 40-55℃; ④ After the paint cools to room temperature, add adhesion promoter and stir evenly. The fineness requirement is: ≤60μm. (2) Preparation of component B: ① Add modified phenolic amine curing agent, special amine curing agent and environmentally friendly solvent according to the formula, and stir thoroughly at medium speed for 15 to 30 minutes; (3) When using, the component A and the component B are fully mixed in proportion to obtain a high-solid epoxy zinc-rich primer, and the mass ratio of the component A to the component B is 12:1 to 26:1; Step 3. The middle coating is a high-solid epoxy micaceous iron intermediate paint, and its raw materials are divided into component A and component B. The specific composition is as follows: The composition of component A by mass is as follows: Epoxy resin 25-35 parts, active diluent 2-5 parts, environmentally friendly solvent 3-8 parts, thixotropic agent 1-2 parts, film-forming aid 1-3 parts, filler 10-20 parts, 1250 mesh ultrafine modified barium sulfate 15-25 parts, pigment powder 3-6 parts; The composition of component B by mass is as follows: 40-60 parts of polyamide curing agent, 10-20 parts of fatty amine curing agent, 10-20 parts of environmentally friendly solvent; Step 4. The preparation method of high solid epoxy micaceous iron intermediate paint is as follows: (1) Preparation of component A: ①Mix epoxy resin, active diluent and environmentally friendly solvent evenly and stir at low speed for 10 to 15 minutes; ② Add thixotropic agent and film-forming agent and disperse at high speed for 15 to 25 minutes; ③ Add filler, 1250 mesh ultrafine modified barium sulfate and pigment powder, disperse at high speed for 25-40 minutes after adding, and control the temperature at 40-55℃; (2) Preparation of component B: ① Add polyamide curing agent, fatty amine curing agent and environmentally friendly solvent according to the formula, and stir thoroughly at medium speed for 15 to 30 minutes; (3) When using, component A and component B are fully mixed in proportion to obtain a high-solid epoxy micaceous iron intermediate paint, and the mass ratio of component A to component B is 8:1 to 12:1; Step 5. The topcoat is a high-solid polyurethane topcoat, and its raw materials are divided into component A and component B. The specific composition is as follows: The composition of component A by mass is as follows: 40-60 parts of high solid low viscosity modified hydroxypropylene resin, 3-8 parts of environmentally friendly solvent, 0.5-2 parts of thixotropic agent, 2-6 parts of functional powder, 3-8 parts of filler, 15-30 parts of pigment powder, 0.5-1.5 parts of ultraviolet light absorber, 0.5-2 parts of light stabilizer; The composition of component B by mass is as follows: 70-80 parts of HDI trimer curing agent, 20-30 parts of environmentally friendly solvent; Step 6. The preparation method of high solid polyurethane topcoat is as follows: (1) Preparation of component A: ①Mix high-solid low-viscosity modified hydroxypropylene resin and environmentally friendly solvent evenly, and stir at low speed for 10 to 15 minutes; ② Add thixotropic agent and additives and disperse at medium speed for 10 to 15 minutes; ③ Add fillers, pigment powders and functional powders, disperse at high speed for 25-40 minutes after adding, and control the temperature at 40-55℃; ④ Grind the above slurry into a sand mill until the fineness is ≤25μm; ⑤Finally, add the UV absorber and light stabilizer and disperse at medium speed for 10 to 15 minutes; (2) Preparation of component B: ① Add HDI trimer curing agent and environmentally friendly solvent according to the formula, and stir thoroughly at medium speed for 15 to 30 minutes; (3) When in use, component A and component B are fully mixed in proportion to obtain a high-solid polyurethane topcoat, and the mass ratio of component A to component B is 6:1 to 10:
1.
2. The process for preparing a large-scale oil storage tank outer surface anti-corrosion coating as claimed in claim 1, characterized in that: In step 1, the epoxy resin is liquid epoxy resin DER 331; the environmentally friendly solvent is propylene glycol methyl ether acetate; the thixotropic agent is one or a mixture of two or more of organic bentonite 140, bentonite 979, and polyamide wax powder HX-9110; the filler is zinc powder treated by dry method and high-energy ball milling technology and with multi-layer coating; the adhesion promoter is A-187; the special amine curing agent is one or more of MD650, MD531E of Eastern America, and NX-5454 curing agent of Cardolite.
3. The process for preparing a large-scale oil storage tank outer surface anti-corrosion coating as claimed in claim 1, characterized in that: In step 2, the low speed is 400-600 r / min; the medium speed is 600-800 r / min.
4. The process for preparing a large-scale oil storage tank outer surface anti-corrosion coating as claimed in claim 1, characterized in that: In step three, the epoxy resin is liquid epoxy resin E51; the active diluent is cardanol glycidyl ether; the environmentally friendly solvent is propylene glycol methyl ether acetate; the thixotropic agent is one or a mixture of two or more of organic bentonite 140, bentonite 979, and polyamide wax powder HX-9110; the film-forming aid is hydroxyethyl cellulose; the filler is 800 mesh flake mica iron oxide; the pigment powder is rutile titanium dioxide; the polyamide curing agent is one or more of Sanmu's 650, Junjiang's D8115, and Guodu's KH-500 curing agent.
5. The process for preparing a large-scale oil storage tank outer surface anti-corrosion coating as claimed in claim 1, characterized in that: In step 4, the low speed is 400-600 r / min; the medium speed is 600-800 r / min; and the high speed is 1000-1100 r / min.
6. The process for preparing a large-scale oil storage tank outer surface anti-corrosion coating as claimed in claim 1, characterized in that: In step five, the high-solid, low-viscosity modified hydroxypropylene resin is Diana LR-7765; the functional powder is 1250 mesh ultrafine polytetrafluoroethylene powder; the filler is 1250 mesh ultrafine modified barium sulfate; the pigment is rutile titanium dioxide; the ultraviolet light absorber is 2-(2H-benzotriazole-2-yl)-4,6-di-tert-amylphenol; the light stabilizer is mono(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate; the thixotropic agent is one or a mixture of two or more of fumed silica A200, polyethylene wax slurry 202P, and silicone bentonite 979; the HDI trimer curing agent is Bayer's aliphatic polyisocyanate; and the environmentally friendly solvent is propylene glycol methyl ether acetate.
7. The process for preparing a large-scale oil storage tank outer surface anti-corrosion coating as claimed in claim 1, characterized in that: In step six, the low speed is 400-600 r / min; the medium speed is 600-800 r / min; and the high speed is 1000-1100 r / min.
Citation Information
Cited By
Anti-corrosion coating for submarine conveying pipeline and preparation process of anti-corrosion coating
CN120648329A